PENERAPAN MODEL TEAM ASSISTED INDIVIDUALIZATION BERBANTUAN GOOGLE CLASSROOM UNTUK MENINGKATKAN KETERAMPILAN KOLABORATIF DAN HASIL BELAJAR AKUNTANSI KELAS XI SMK NEGERI 1 MEDAN - Vincentia Sinaga; Choms Gary Ganda Tua Sibarani; La Hanu; Tuti Sriwedari; Weny Nurwendari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study is the low level of collaborative skills and accounting learning outcomes among 11th-grade students in Class AKL 4 at SMK Negeri 1 Medan. This study aims to determine the improvement in students’ collaborative skills and accounting learning outcomes through the application of the Team Assisted Individualization learning model supported by Google Classroom. This study was conducted at SMK Negeri 1 Medan during the 2025/2026 academic year with 36 students from Class XI AKL 4 as the research subjects. This study is a Classroom Action Research (PTK) project conducted in two cycles, with each cycle consisting of the planning, implementation, observation, and reflection stages. The data collection techniques used were interviews, observations, tests, and documentation, while the data analysis techniques employed both qualitative and quantitative methods. The results showed that collaborative skills increased from 51.25% in Cycle I to 79.17% in Cycle II. Student learning outcomes also improved in each cycle. In the pre-test, 9 students (25%) met the proficiency standard with an average score of 58.52. After the Cycle I intervention, the number of students who met the proficiency standard increased to 20 students (55.56%) with an average score of 74.36. In Cycle II, the number of students who met the proficiency standard increased to 32 students (88.89%) with an average score of 82.25. Thus, it can be concluded that the implementation of the Team-Assisted Individualization learning model using Google Classroom can improve the collaborative skills and accounting learning outcomes of 11th-grade students in Class AKL 4 at SMK Negeri 1 Medan.